Efficient perovskite solar cells employing a simply-processed CdS electron transport layer. Issue 38 (21st September 2017) - Dong, Jia; Wu, Jihuai; Jia, Jinbiao; Fan, Leqing; Lin, Yu; Lin, Jianming; Huang, Miaoliang
Abstract : In this report, redispersable CdS nanoparticles are synthesized via a specific one-step solvothermal reaction and are employed as electron-selective materials for organometal halide perovskite solar cells. Abstract : In this report, redispersable CdS nanoparticles are synthesized via a specific one-step solvothermal reaction and are employed as electron-selective materials for organometal halide perovskite solar cells. The as-synthesized CdS nanoparticles can be well re-dispersed in toluene to form a uniform and stable CdS ink. On this basis, a CdS electron-selective contact layer can be directly prepared by spin-coating CdS ink and without a further annealing process. The CdS electron-selective contact layer has high optical transmittance at visible wavelengths. Its electron extraction and transfer properties are also investigated using current density–voltage curves, incident photocurrent conversion efficiency, stabilized current density and photoluminescence spectra. The use of a CdS electron-selective contact layer in a planar perovskite solar cell equipped with a Cs0.05 (MA0.17 FA0.83 )0.95 Pb(I0.83 Br0.17 )3 light-absorption layer results in a high power conversion efficiency of 16.5%.